Penguatan Ekspor Komoditas Suku Cadang Kendaraan Indonesia di Meksiko Melalui Peran INA-LAC Business Forum - Laowo, Darnell Petra Clement; Simanjuntak, Triesanto Romulo; Ismoyo, Petsy Jessy (Global Political Studies Journal, 2025)
The automotive component manufacturing ecosystem, particularly in Indonesia and Mexico, shows significant differences. This refers to the diversification of production in both Indonesia and Mexico, which results in product differences. Mexico sees Indonesia as being able to meet its domestic demand for automotive components. On the other hand, Indonesia sees Mexico as a new market for its commodities. However, as a step to connect the two countries to meet their respective market needs, the INA-LAC Business Forum serves as a platform to facilitate interaction between the two countries and strengthen their relationship, particularly in the areas of economy and trade. This study will focus on the INA-LAC Business Forum, which aims to serve as a bridge for both countries to explore each other's markets and its impact on the export of vehicle spare parts. This study is a descriptive qualitative study that uses secondary data collected through a literature review. This study uses David Ricardo's theory of comparative advantage and the concepts of liberal diplomacy and free trade, whereby this study can show that vehicle spare parts commodities can be facilitated to enter the Mexican market through the existence of a business forum Keywords— Bilateral Relations, Economy Diplomacy, Indonesia, Mexico, Vehicle Parts